Using megatrends as a navigation tool for the future library - Mittrowann, Andreas (Access: An International Journal of Nepal Library Association, 2023)
The author first discusses the informative value of forecasts and then focuses on12 so-called megatrends developed by the German Zukunftsinstitut in Frankfurt/Main (“Future Institute”), which claim long-term informative value for themselves: Knowledge Culture, Connectivity, Neo-Ecology, Urbanization, Mobility, Globalization, New Work, Individualization, Silver Society, Health, Security and Gender Shift are presented with their various facets and the respective relevance for libraries is discussed in bullet points. In addition, the 20 topics of the IFLA Trend Report 2021, updates are assigned to the respective megatrends to round them off. The original version of this article appeared in issue 25 (2022) No. 6 of the German library journal b. i. t. online.